ETIO-PATHOGENETIC ASPECTS OF THROMBOCYTOPENIA - Isakulova Muhabbat Mardanovna; Ibragimova Nadiya Sabirovna; Kulmatova Shahnoza (Web of Journals Publishing, 2025)
Thrombocytopenia, characterized by a decrease in the level of platelets in the blood, is an urgent and multifaceted problem in modern medicine. It can result from a variety of causes, including decreased platelet production in the bone marrow, increased platelet destruction, or sequestration in the spleen. It is important to note that thrombocytopenia can serve as a marker for various diseases, such as infections, autoimmune disorders, and even malignancies. This problem requires an interdisciplinary approach involving both hematologists and other specialists, which emphasizes the importance of a comprehensive understanding of thrombocytopenia to improve the quality of life of patients.
Keywords: Thrombocytopenia, pathogenesis, autoimmune thrombocytopenia, antiplatelet antibodies, immunological diagnostics.